Potential Roles of Sestrin2 in Alzheimer’s Disease: Antioxidation, Autophagy Promotion, and Beyond - Shang-Der Chen; Jenq-Lin Yang; Yi-Heng Hsieh; Tsu-Kung Lin; Yi-Chun Lin; A-Ching Chao; Ding-I Yang (Biomedicines, 2021)
Alzheimer’s disease (AD) is the most common age-related neurodegenerative disease. It presents with progressive memory loss, worsens cognitive functions to the point of disability, and causes heavy socioeconomic burdens to patients, their families, and society as a whole. The underlying pathogenic mechanisms of AD are complex and may involve excitotoxicity, excessive generation of reactive oxygen species (ROS), aberrant cell cycle reentry, impaired mitochondrial function, and DNA damage. Up to now, there is no effective treatment available for AD, and it is therefore urgent to develop an effective therapeutic regimen for this devastating disease. Sestrin2, belonging to the sestrin family, can counteract oxidative stress, reduce activity of the mammalian/mechanistic target of rapamycin (mTOR), and improve cell survival. It may therefore play a crucial role in neurodegenerative diseases like AD. However, only limited studies of sestrin2 and AD have been conducted up to now. In this article, we discuss current experimental evidence to demonstrate the potential roles of sestrin2 in treating neurodegenerative diseases, focusing specifically on AD. Strategies for augmenting sestrin2 expression may strengthen neurons, adapting them to stressful conditions through counteracting oxidative stress, and may also adjust the autophagy process, these two effects together conferring neuronal resistance in cases of AD.